PERAN HUMAS DALAM MENINGKATKAN LAYANAN PUBLIK DI KANTOR WILAYAH KEMENKUMHAM SUMATERA UTARA - Mega Ulva Sari Sihombing; Rachel Mia Lorenza Lbn. Toruan; Nurleli Nurleli (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: In government organizations, public relations provide citizens with access to necessary information, prioritizing their interests to uphold principles of good governance. Public information transparency plays a crucial role; furthermore, the information conveyed must be accurate, clear, and timely. The Regional Office of the Ministry of Law and Human Rights in North Sumatra also serves as a public information portal, collaborating with mass media to disseminate information to public. This study examines the role of public relations in enhancing the quality of public services at the Regional Office of the Ministry of Law and Human Rights (Kemenkumham) in North Sumatra. Employing a descriptive qualitative approach, the study illustrates the public relations function as a communication liaison, relationship manager, and positive image builder, all aimed at supporting effective, transparent, and responsive public services. The findings indicate that public relations actively disseminate information, facilitates communication between the government and the public, and builds public trust to improve the quality of legal administration and human rights services. Keywords: Public Relations; Public Services; Communication; Ministry of Law and Human Rights; North Sumatra   Abstrak: Dalam organisasi pemerintah, humas memberi warga akses terhadap informasi yang mereka butuhkan, memprioritaskan kepentingan mereka untuk memastikan permasalahan pemerintahan yang baik. Transparansi informasi publik memainkan peran yang sangat penting. prinsip-prinsip pemerintahan yang baik; selanjutnya, informasi yang disampaikan harus akurat, sederhana, dan cepat. Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Sumatera Utara juga berfungsi sebagai portal informasi publik, bekerja sama dengan media massa untuk menyebarkan informasi kepada masyarakat secara luas. Penelitian ini mengkaji peran humas dalam meningkatkan kualitas layanan publik di Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia (Kemenkumham) Sumatera Utara. Dengan menggunakan pendekatan kualitatif deskriptif, penelitian ini menggambarkan fungsi humas sebagai penghubung komunikasi, pengelola hubungan, dan pembentuk citra positif guna mendukung layanan publik yang efektif, transparan, dan responsif. Hasil penelitian mengindikasikan bahwa humas aktif menyampaikan informasi, memfasilitasi komunikasi antara pemerintah dan masyarakat, serta membangun kepercayaan publik untuk meningkatkan mutu layanan administrasi hukum dan hak asasi manusia. Kata kunci: Humas; Layanan Publik; Komunikasi; Kemenkumham; Sumatera Utara